2017
DOI: 10.5455/njppp.2017.7.0623506072017
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial prescribing pattern in urinary tract infection in a tertiary care hospital

Abstract: Background: Urinary tract infection (UTI) is a common illness affecting both males and females in almost all age groups. Varieties of antimicrobials such as cotrimoxazole, nitrofurantoin, fluoroquinolones, and penicillin are effective for treatment of UTI. Aims and Objectives: The present observational study was planned to generate data on antimicrobial use pattern in UTI which could be beneficial in selection of rational drug therapy in UTI. Materials and Methods: The retrospective study was carried out by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Total of 121 antibiotics were prescribed in 84 UTI patients among which Cefoperazone + sulbactam (23.97%) was mostly prescribed followed by amikacin (14.88%) and piperacillin + tazobactam (14.05%). Similar results were observed in the study conducted by Samira Kumar Naik et al, where it was observed that cephalosporins are the mostly prescribed antibiotics in the management of UTI [23].…”
Section: Comparision Of Total Cost Of Antibioticssupporting
confidence: 89%
“…Total of 121 antibiotics were prescribed in 84 UTI patients among which Cefoperazone + sulbactam (23.97%) was mostly prescribed followed by amikacin (14.88%) and piperacillin + tazobactam (14.05%). Similar results were observed in the study conducted by Samira Kumar Naik et al, where it was observed that cephalosporins are the mostly prescribed antibiotics in the management of UTI [23].…”
Section: Comparision Of Total Cost Of Antibioticssupporting
confidence: 89%
“…Samira et al, study was similar to our study in which the ceftriaxone was the highest prescribed among the cephalosporins. 14 Among 50 patients, subjects with age group 18-33 are mostly affected with uUTIs 23 (46%). illiterate (52%) was predominantly affected with uUTI when compared to literate (48%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the nature and pattern of antimicrobial prescribing practice changes with time as spectrum of pathogens change and new antimicrobials are introduced. [3][4][5][6][7][8][9][10][11][12][13][14] Culture sensitivity tests were also important in case of UTI to go for a specific antibiotic treatment rather than the empirical treatment for the patients. 15,16 Ideally, the antimicrobial agent chosen should be well tolerated, well absorbed, achieve high urinary concentrations, and have a spectrum of activity limited to the known or suspected pathogen(s).…”
Section: Introductionmentioning
confidence: 99%